PERSEPSI GURU TENTANG PRAKTIK KEPEMIMPINAN DAN MANAJEMEN SEKOLAH DALAM MENGEMBANGKAN ORGANISASI PEMBELAJAR - Permana, Johar; Maruli, Sahat (Universitas Pendidikan Indonesia, 2016)
This study determines the extent to which the relationship between teacher perceptions of effective of school leadership and management in developing organizational learning and Mathematics and Science teachersâ€™ academic optimism of Junior High School in Pangkal Pinang District. This study uses a quantitative approach with the descriptive correlational method and multivariate analysis. The number of samples is 60 teachers. The instrument is self-administered and Likert scale model survey. Results of hypothesis testing showed positive and significant relationship between teacher perceptions of leadership and management of school practices in developing an organizational learning and academic optimism of teachers, while the context have both positive and negative correlation with teacher academic optimism.Â Keywords: organizational learning, self-evaluation, academic optimismÂ